The role of vitamin D status in the bioenergetics of inflammation - Calton, Emily Kathleen (Curtin University, 2017)
This thesis investigates the role of vitamin D metabolites 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D in human bioenergetics and inflammation. The evidence presented comes from a narrative review, two systematic reviews, two cross-sectional studies and an observational longitudinal study design. Collectively, the thesis supports a modulatory role for vitamin D in whole body and cellular bioenergetics and inflammation. Future studies could build on these findings; establishing a causal role for vitamin D in inflammation and energy metabolism.